Reach-to-grasp movements in Macaca fascicularis monkeys: the Isochrony Principle at work - Sartori, Luisa; Camperio, Andrea; Bulgheroni, Maria; Castiello, Umberto (Frontiers in Psychology, 2013)
Humans show a spontaneous tendency to increase the velocity of their movements depending on the linear extent of their trajectory in order to keep execution time approximately constant. Termed the isochrony principle, this compensatory mechanism refers to the observation that the velocity of voluntary movements increases proportionally with their linear extension. Although there is a wealth of psychophysical data regarding isochrony in humans, there is none regarding non-human primates. The present study attempts to fill that gap by investigating reach-to-grasp movement kinematics in free-ranging macaques. Video footage of monkeys grasping objects located at different distances was analyzed frame-by-frame using digitalization techniques. The amplitude of arm peak velocity was found to be correlated with the distance to be covered, and total movement duration remained invariant although target distances varied. Like in humans, the ‘isochrony principle’ seems to be operative as there is a gearing down/up of movement velocity that is proportional to the distance to be covered in order to allow for a relatively constant movement duration. Based on a centrally generated temporal template, this mode of motor programming could be functional in macaques given the high speed and great instability of posture and joint kinematics characterizing their actions. The data presented here take research in the field of comparative motor control a step forward as they are based on precise measurements of spontaneous grasping movements by animals living/acting in their natural environment.